Real-time multimodal imaging of daptomycin action on the cell wall of adherent Staphylococcus aureus - Alexis Canette; Rym Boudjemaa; Julien Deschamps; Karine Steenkeste; Christian Marlière; Romain Briandet; Marie-Pierre Fontaine-Aupart (BMC Research Notes)
Abstract Objectives This study investigated the efficacy of daptomycin against adherent Staphylococcus aureus (S. aureus), a common colonizer of medical devices that leads to severe infections. For the first time, we evaluated the bactericidal effects of daptomycin on S. aureus immediately after adhesion, mimicking early-stage contamination of biomaterials. Time-kill curve assay and confocal laser scanning microscopy (CLSM) were used to analyze the process dynamics. In addition, atomic force microscopy (AFM) and scanning electron microscopy (SEM) were employed to elucidate daptomycin-induced structural changes in the bacterial cell wall. Results description Daptomycin, at clinically relevant concentrations, rapidly eradicated adherent bacteria in the exponential growth phase, demonstrating an efficiency comparable to its action against planktonic cells. Prolonged exposure to the antibiotic caused marked alterations in the bacterial cell wall, including surface roughening and perforation, as revealed by multimodal imaging. However, daptomycin effectiveness diminished as biofilm formation progressed, underscoring the need for further exploration of optimized clinical strategies.